Effect of Saline Waters on Pearl Millet Under Drought
A study on the influences of saline waters (composition similar to local ground waters) at the critical pre-flowering stage of pearl millet (cv. BJ-104) crop, under drought and undroughted conditions, revealed that a significantly higher dry matter production and grain yield can be achieved if the water stress is avoided through irrigation with sub-standard waters (160 me